Examining the Correlation of Self-Efficacy, Work Experience, and Openness to Change: Can Academia Embraces Change? - Said Alwi; Mutia Sari; Radzuan Sukor (Institut Agama Islam Negeri Lhokseumawe, 2024)
This study aims to analyze the correlation between self-efficacy, work experience, and openness to change within the academic circle of the State Islamic Institute of Lhokseumawe. This study employs a quantitative research method with a correlational design. The research population includes all academic staff of the institution, consisting of lecturers and educational staff. The research sample consisted of 160 respondents, comprising 100 lecturers spread across four faculties —the Faculty of Sharia (21 people), the Faculty of Education and Teacher Training (44 people), the Faculty of Economics and Islamic Business (21 people), and the Faculty of Ushuluddin, Adab, and Dakwah (14 people)—and 60 educational staff. The sample was selected using convenience sampling techniques, taking into account the representation of each faculty and job category. The data were analyzed using descriptive analysis, Pearson's correlation, and multiple regression. The results showed a significant positive correlation between self-efficacy and openness to change, with a higher correlation coefficient in the lecturer group (r = 0.50) than in the educational staff group (r = 0.38). Furthermore, these findings indicate that individuals with high self-efficacy tend to be more open to change. In terms of work experience, respondents with less than five years of service showed more openness to change (r = 0.50) than respondents with more than ten years of service (r = 0.35). This indicates a tendency for resistance to change to increase with length of service.